Luxação lateral de patela em um Poodle toy - Dal-Bó, Ísis dos Santos; Ferreira, Márcio Poletto; Alievi, Marcelo Meller; Silva, Luciana Machado da; Nóbrega, Fernanda Silveira; Gonzalez, Paula Cristina Sieczkowski; Beck, Carlos Afonso de Castro (Acta Scientiae Veterinariae, 2018)
Background : : : : Luxating patella is one of the most frequent conditions of the stifle joint in dogs and it can evolve into a degenerative joint disease. The occurrence of the condition can be medial or lateral, unilateral or bilateral. Its origin can be traumatic or congenital and, additionally, it may undergo genetic and environmental influence. Lateral luxation is more common in large breed dogs, and it can rarely affect medium and small breeds, whilst medial luxation is more common in small breed dogs. The classification of patellar luxation comprises four grades, according to the patellar position, clinical signs and seriousness of the bone deformities found. The diagnosis is made based on the clinical evaluation, associated with a radiographic evaluation. The present study aims at describing a case of bilateral grade 3 lateral luxating patella in a Toy Poodle dog. Case: A five-month-old female Toy Poodle dog was presented for difficulty standing and claudication of hind limbs. Orthopedic evaluation revealed internal rotation of the stifle, claudication of hind limbs during walking and “jumps” during trotting, in addition to a lateral grade 3 luxating patella and slight restriction of the joint motion upon extension of the right and left hind limbs. Radiographic evaluation of both stifles evidenced an ectopic (lateral) position of the right and left patellas. The animal was referred to the surgery department, where it was submitted to surgical intervention of both stifles. A reduction of luxation in both stifles was achieved through medial arthrotomy, wedge recession trochleoplasty, lateral desmotomy and medial imbrication of the articular capsule techniques. Tramadol hydrochloride, dipyrone and meloxicam were prescribed as postoperative medication. Daily wound care, resting and mild walks using a lead were recommended for the animal. On the tenth postoperative day, the stitches were removed from the skin and the animal seemed to be in a good general state, using adequately its hind limbs when walking and trotting. Discussion: The medial form of the congenital patellar luxation is common both in large and small breeds. However, the lateral form is more common in large or giant breeds, differently to the findings of the present case, in which luxation occurred in a Toy Poodle. Surgery is recommended in animals with a luxating patella grade starting from 2, as even the smallest luxation grades may evolve into higher grades, causing functional inability of the limb and degenerative joint disease. Surgery was justified in this case, because the animal presented a grade 3 luxating patella. The decision on which technique should be used will depend on the luxating patella grade and on soft tissue compromise. The most recommended procedure is a combination of various techniques in the same articulation. In this case, the use of wedge recession trochleoplasty and medial imbrication of the articular capsule techniques was successful, as a few days after surgery the animal was able to walk adequately without presenting any instability of the patellas, thus improving its quality of life. Moreover, upon reaching adulthood, the animal maintained an adequate gait, without excessive patellar motion.